Organized labour migration of residents of Lithuania to the USSR in the sixth–ninth decades of the 20th century - Stravinskienė , Vilija (Genocidas ir rezistencija, 2017)
Referring to archive and historiographic materials, in this paper problematics of labour migration to the USSR from Lithuania in 1953-1984 is analysed. Attention is drawn to migration directions, motivation of residents, quantitative indices, territorial aspects related to persons participating in labour migration process and social picture. Residents of Lithuania became participants of the campaign for organized all Soviet Union-wide labour force migration to participate in implementation of large and important land, forestry and industry projects. By the way, the residents of our Republic joined this campaign later than residents from other Republics – in 1953 only. Organized labour force migration from Lithuania to the USSR was of lower level that it had been planned in Moscow. The main directions of labour force migration were: 1) agriculture intensification program (virgin lands campaigns in Kazakhstan and Russia); 2) Russian forestry development program; 3) program of construction of gigantic transport and industrial objects in Russia (Siberia, etc.); 4) the “Third Semester” program – season-based works of students in industry and agriculture sectors of Russia, Kyrgyzstan, Uzbekistan and other Soviet Republics. In 6th-9th decades of the 20th century, about 75 thousand residents of Lithuanian Soviet Socialist Republic were sent to work in other regions of the Soviet Union; labour migrants worked on industrial objects, farms and forestry units. Mostly, they were men from urban areas, by ethnic composition – Russians and Lithuanians. The most intensive time period of sending to work as labour migrants was the 1953-1965 period, as at that time in Kazakhstan and Russia huge programs of economic development had been implemented (virgin lands campaign, forestry development). Namely during this period, over 80 per cent of residents of Lithuania who participated in this campaign were sent to labour destinations. Although in later years the migration campaign covered entire Lithuania, its scale diminished markedly. Due to certain national traits of Lithuanians (sedentary life, attachment to the land) and social-economic situation in the Lithuanian Soviet Socialist Republic (fast and intensive industry development ensuring quite good wages, well-developed social infrastructure, etc.), the residents of Lithuania liked to conclude short-term employment agreements, and after termination of these agreements made efforts to return to Lithuania and stay there not attracted by labour migration campaign anymore.